Model of Cation Transportation Mediated by High-Affinity Potassium Transporters (HKTs) in Higher Plants. Issue 1 (December 2015) - Su, Yi; Luo, Weigui; Lin, Wanhuang; Ma, Liying; Kabir, Mohammed
Abstract Trk/Ktr/HKT transporters probably were evolved from simple K+ channels KcsA. HKT transporters, which mediate Na+ -uniport or Na+ /K+ -symport, maintain K+ /Na+ homeostasis and increase salinity tolerance, can be classified into three subfamilies in higher plants. In this review, we systematically analyzed the characteristics of amino acids sequences and physiological functions of HKT transporters in higher plant. Furthermore, we depicted the hypothetical models of cations selection and transportation mediated by HKT transporters according to the highly conserved structure for the goal of better understanding the cations transportation processes.